Workshop Klinik Penulisan Jurnal Nasional Penelitian dan Pengabdian Masyarakat sebagai Upaya Pengembangan Kapasitas Sumber Daya Pengajar - Yoga Dwi Jatmiko; Bunga Hidayati; Bambang Semedi; Yusuf Efendi; Ahmad Nuril Fuad Al Fatih; Isdiantoni; Ida Ekawati; Endry Nugroho Prasetyo; Koentjoro, Maharani Pertiwi (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
Currently, many teaching resources have not fully understood how to write and submit to a journal. This can be attributed to various factors, such as a lack of training or experience in journal writing, a greater focus on teaching or research activities, or limited opportunities to engage in journal writing communities. Therefore, this workshop aims to enhance the capacity of teaching resources in writing and publishing research and community service in national journals. The implementation method consists of preparation, activity execution, mentoring, and evaluation stages. The results of the activity evaluation show that 80% of participants have improved their abilities to comprehend the structure of scientific journals, writing ethics, effective writing techniques, and 100% of participants are capable of drafting journals according to environmental style guidelines. Measured capacity development of teaching resources enables them to write journals in accordance with the guidelines of each publisher, avoiding rejection. Furthermore, the ability to understand the Open Journal System (OJS) application during submission is essential for teaching resources to publish in nationally accredited journals.